1988
DOI: 10.1161/01.res.63.6.1060
|View full text |Cite
|
Sign up to set email alerts
|

Two structurally distinct calcium storage sites in rat cardiac sarcoplasmic reticulum: an electron microprobe analysis study.

Abstract: The elemental composition of subcellular organelles in resting rat papillary muscle was measured by electron probe x-ray microanalysis of cryosections of flash-frozen tissue. Nonmitochondrial electron-dense structures (50-100 nm in diameter) with a phosphorous concentration larger than 375 mmol/kg dry wt were identified in the interfibrillar spaces of the I band region. They were not visible in the proximity of transverse tubules. The sodium, magnesium, phosphorus, sulfur, chlorine, and potassium content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…2 values of ∼50 mM [58,59], assuming 20% dry weight. Similar variation ranges were reported for SR, i.e., between 6 mM [24], 15 [23], 20 [22] and 33 mM [60], or for ER in different cells, i.e., between 1 mM [6], 1.5 to 2.5 [11], 3 [36], and 9.5 mM [7]. In sum, if one disregards excessively high values reported in older references for all of these systems, it appears reasonable to assume a total of ∼5 mM Ca 2+ in alveolar sacs.…”
Section: Discussionsupporting
confidence: 83%
“…2 values of ∼50 mM [58,59], assuming 20% dry weight. Similar variation ranges were reported for SR, i.e., between 6 mM [24], 15 [23], 20 [22] and 33 mM [60], or for ER in different cells, i.e., between 1 mM [6], 1.5 to 2.5 [11], 3 [36], and 9.5 mM [7]. In sum, if one disregards excessively high values reported in older references for all of these systems, it appears reasonable to assume a total of ∼5 mM Ca 2+ in alveolar sacs.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with the documented propensity of mitochondria and sarcoplasmic reticulum to accumulate calcium when cells are presented with an excess calcium load (1,31,32,(35)(36)(37)(38). EPMA measurements also showed that the elevated calcium in the mitochondrial and extramitochondrial sites was associated with increased phosphorus, indicating the formation of calcium phosphate precipitates (10,31,32).…”
Section: Discussionsupporting
confidence: 77%
“…However, in multicellular ventricular preparations, elevated diastolic YCamito has not been reported up to now. Not only unpotentiated ventricular trabeculae have a XCamito below the detection limit (Wendt-Gallitelli, 1986;Joergensen et al 1988). In guinea-pig ventricular trabeculae potentiated with paired pulses (Wendt-Gallitelli, 1986) or in hamster hearts beating at 4 Hz (Bond et al 1989), ECamito was not significantly different from zero.…”
Section: Mitochondriamentioning
confidence: 88%
“…Using EPMA, ECaSR can be shown to have the properties expected from the functional Ca2+ store (Wendt-Gallitelli, Jacob & Wolburg 1982;Wendt-Gallitelli, 1985, 1986Wheeler-Clark & Tormey, 1987;Joergensen et al 1988;Bond et al 1989). During diastole, XCaSR in junctional SR and corbular SR was significantly higher than ECamyo; this difference disappeared during early systole and reappeared during late systole.…”
Section: Calcium In the Sarcoplasmic Reticulummentioning
confidence: 99%